Pleural effusion aetiology, presentation, treatment and outcome in haematological diseases: a review: Pleural effusions in haematologic diseases - Fantin, Alberto; Castaldo, Nadia; Vailati, Paolo; Morana, Giuseppe; Orso, Daniele; Vetrugno, Luigi; Patruno, Vincenzo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Pleural effusions (PE) can complicate the course of hematologic disorders (HD) and may arise in the form of malignant PE or as a consequence of non-neoplastic complications. While a certain amount of data has been published regarding infectious and iatrogenic HD-associated PE (HPE), no comprehensive review regarding the other types of HPE has ever been conducted. To address this issue, we performed a systematic review of the literature regarding HPE, focusing on the clinical and chemical characteristics of PE, therapeutic approaches and ì outcomes at the one-year follow-up. Methods: We conducted our review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Overall, 283 manuscripts and 1216 cases were included. In summary, PE frequently signals an underlying HD, especially Hodgkin’s lymphoma and IgG4-related disease; it mainly consists of exudate, although chylothorax is diagnosed in some cases. Although cytological examination has a discrete diagnostic yield, it is generally insufficient to render a definitive diagnosis; pleural biopsy remains an important diagnostic means in such cases. Invasive diagnostic procedures are not frequently performed because of an increased risk of haemorrhagic complications. The majority of PE are resolved by means of systemic therapy. When local treatments are attempted, the most frequently adopted procedures are evacuative thoracentesis and indwelling chest tube placement Conclusions: This review highlights the need for well-designed prospective studies comparing diagnostic means and therapeutic interventions for HPE to increase the quality of available data. (www.actabiomedica.it)